Identifying missing people: the contribution of forensic dentistry and DNA - Luciene Menrique CORRADI (Revista de Odontologia da UNESP, 2017)
Abstract Introduction Human identification is considered one of the major steps concerning missing people. The Forensic Anthropology Sector of Legal Medical Institutes identifies corpses. Forensic dentistry and DNA tests stand out among the existing standard tests. Objective This article aimed to evaluate human identification effectiveness through forensic dental examination performed in the forensic anthropology sector in a Forensic Medical Institute, comparing them with DNA analyses. Methodology This is a cross-sectional study using secondary data available in the department´s database, from 2008 to 2014, concerning identification procedures using forensic dentistry and DNA techniques. Result The analysis of the examinations eligible to this study (241) showed that DNA analysis was the method used for identification in 79.3% of the cases and forensic dental examinations were used in 20.7% of the cases. As for the type of biological material used during these examinations, unidentified corpses corresponded to 131 cases (53.9%), skeleton structures corresponded to 109 cases (44.9%) and there were 3 cases of body segments (1.2%). When analyzing the time spent to complete the tests, dental examinations were faster than DNA tests. The time spent for forensic dental examination does not depend on the type of dental documentation evaluated. Conclusion The analysis of the results in this study showed that human identification through forensic dentistry is effective, rapid and less costly, contributing to greater agility in solving issues related to locating missing people.